Building sustainable market linkages through innovations platforms for technology adoption: Case studies from Uganda, Kenya and Tanzania. - Mayanja, S.; McEwan, M.; Obong, Y.; Manasseh, R.; Ndolo, P.; Lukonge, E. (2012)
Finding and sustaining markets for Orange-fleshed sweetpotatoes is a challenge in many parts of East Africa. Farmers face numerous difficulties in identifying credible business partners, while traders and other market chain actors are frustrated by inconsistencies in supply. In the Dissemination of New Agricultural Technology in Africa (DONATA) OFSP project, Innovation Platforms for Technology Adoption (IPTAs) in Ethiopia, Kenya, Rwanda, Tanzania and Uganda have brought together relevant value chain stakeholders to develop institutional mechanisms which have supported the up-scaling of OFSP technologies (e.g. new varieties, agronomic practices, and post-harvest activities) and marketing strategies. This paper presents key strides attained in accessing equitable markets by IPTAs in three DONATA project countries. While some IPTAs have segmented the market and differentiated the producer groups along product lines, others have supported various chain actors to strengthen their businesses thus increasing throughput to the markets. Hence in the former case, groups are classified along major OFSP products marketed (vines, roots and processed products), while in the latter, specialized actors take on these functions. Successes include firm contracts for supply of OFSP flour to supermarkets in Kenya, supply of roots to urban markets in Uganda, and sale of vines to individuals and organizations in Tanzania. The major challenges include aligning production to demand for consistent supply, poor market infrastructure and low consumer awareness of the benefits of OFSP. Future prospects lie with newly established relations with big buyers and also working closely with other initiatives to consolidate gains achieved to date.